Diet and feeding behaviour of longnosed skate Dipturus oxyrinchus in the Sardinian waters (central-western Mediterranean) - Mulas A; Follesa M. C; Cannas R; Cau Al; Porcu C; Cau A.; BELLODI, ANDREA; MARONGIU, MARTINA FRANCESCA (2015)
A total of 255 longnosed skate Dipturus oxyrinchus, caught in the Sardinian waters (central-western Mediterranean), were analyzed with respect to fish size and depth, in order to provide information on the diet and the feeding behaviour. Specimens, ranging from 93 to 1153 mm of total length (LT), were collected at depths between 121 and 671 m, during experimental trawl surveys carried out in the period 2005 - 2010. The diet was constituted mainly of crustaceans (%PSIRI = 72.69), teleosts (%PSIRI = 10.28) and molluscs (%PSIRI = 10.94). Levins’ index showed a narrow niche breadth (Bi = 0.35). The trophic level (TROPH) was 3.63 (S.E. = ± 0.5). The analysis showed deep ontogenetic changes in the feeding behaviour. Early life stages were characterized by benthic diet, which turned into benthopelagic during growth. Mysids, and particularly Lophogaster typicus (%PSIRI = 34.51), were the main prey items among immature individuals, replaced by euphausiids, mainly Meganyctiphanes norvegica (%PSIRI = 13.19), among maturing ones. Crustaceans became less important among mature specimens, being substituted by molluscs (%PSIRI = 28.99) and teleosts (%PSIRI = 24.56). A concomitant increasing of the trophic level was recorded (TROPH ± S.E. = 3.41 ± 0.44, 3.75 ± 0.54, 4.28 ± 0.61 for immature, maturing and mature individuals, respectively). These feeding patterns ensured low levels of intraspecific competition.